2021
DOI: 10.1182/blood.2020007155
|View full text |Cite
|
Sign up to set email alerts
|

Natural IgM antibodies inhibit microvesicle-driven coagulation and thrombosis

Abstract: Thrombosis and the complications associated with it are a major cause of morbidity and mortality worldwide. Microvesicles (MVs), a class of extracellular vesicles, are increasingly recognized as mediators of coagulation and biomarkers of thrombotic risk. Thus, identifying factors targeting MV-driven coagulation may help in the development of novel antithrombotic treatments. We have previously identified a subset of circulating MVs that is characterized by the presence of oxidation-specific epitopes and bound b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…B-cell-derived natural IgM recognizes EVs bearing oxidation-specific epitopes and represses their inflammatory signaling and pathological endeavors [ 141 ]. Moreover, natural IgM antibodies inhibit MV-driven coagulation and thrombosis [ 142 ].…”
Section: Evs As Pathophysiological Drivers Of Atherothrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…B-cell-derived natural IgM recognizes EVs bearing oxidation-specific epitopes and represses their inflammatory signaling and pathological endeavors [ 141 ]. Moreover, natural IgM antibodies inhibit MV-driven coagulation and thrombosis [ 142 ].…”
Section: Evs As Pathophysiological Drivers Of Atherothrombosismentioning
confidence: 99%
“…Under in vitro simulated conditions of coagulopathy, EV from different cellular origins (EC and platelet) and at distinct concentrations showed a divergent but procoagulant effect within the coagulation process [ 196 ]. Numerous studies have dissected in vitro and in vivo the procoagulant effect of EVs, mainly MVs, leading to thrombosis [ 142 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 ]. Procoagulant EVs within the necrotic core of atherosclerotic plaques provoke the burst of the coagulation cascade upon plaque rupture [ 169 ] being TF + -MVs the main initiators [ 208 , 209 , 210 ].…”
Section: Evs As Pathophysiological Drivers Of Atherothrombosismentioning
confidence: 99%
“…Circulating IgM antibodies have been found to be part of the complex regulatory system of EV functioning, controlling the coagulant capacity of EVs. Indeed, endogenous IgM antibodies were found to bind to oxidation-specific epitopes in EVs and to modulate EV-mediated coagulation and thrombosis in in vitro and in vivo experiments [ 94 ]. Similarly, circulating EVs participate in vascular homeostasis.…”
Section: Blood Extracellular Vesicles In Physiological Processesmentioning
confidence: 99%
“…[ 26,88 ] For instance, it has been shown that nIgM is capable of removing oxidized lipids (oxLDL), advanced glycation end products (AGE), nucleic acids and other potentially harmful self‐molecules as well as prevent thrombosis. [ 27,89,90 ] In addition, several studies also reported cross‐reactivity of nIgM with insulin, immunoglobulins and LPS. [ 91,92 ] Moreover, studies exploiting transgenic mouse models unable to secrete IgM (sIgM‐/‐) have shown that loss of sIgM results in numerous diseases including atherosclerosis and autoimmunity most likely due to the accumulation of altered self‐molecules.…”
Section: Autoreactive Igm Is Capable Of Destructing or Protecting Selfmentioning
confidence: 99%